Recent advances in mitochondrial turnover during chronic muscle disuse - Liam D. Tryon; Anna Vainshtein; Jonathan M. Memme; Matthew J. Crilly; David A. Hood (Integrative Medicine Research)
Chronic muscle disuse, such as that resulting from immobilization, denervation, or prolonged physical inactivity, produces atrophy and a loss of mitochondria, yet the molecular relationship between these events is not fully understood. In this review we attempt to identify the key regulatory steps mediating the loss of muscle mass and the decline in mitochondrial content and function. An understanding of common intracellular signaling pathways may provide much-needed insight into the possible therapeutic targets for treatments that will maintain aerobic energy metabolism and preserve muscle mass during disuse conditions.